Adult Students of Color in Predominately White Classrooms - Robin Walker Thompson (Adult Education Research Conference, 2006)
This study explored the experiences of adult students of color in predominately white classrooms. My aims were to (a) better understand their educational experiences, (b) share their stories in their respective voices, and (c) conduct a secondary level of data analysis that examined issues of race, class, power, and privilege.
Keywords: Students of color; voice; active interviews